Vascular endothelial growth factor C expression correlates with tumour metastatic recurrence in patients with oesophageal squamous cancer after Ivor-Lewis oesophagectomy - Sun, Zhi-Gang; Wang, Zhou; Ma, Li-Mei; Zhang, Min; Chen, Gang; Liu, Xiang-Yan (Gastroenterology Review/Przegląd Gastroenterologiczny, 2012)
Introduction : Lymph node status is one of the most important prognostic factors for oesophageal squamous cell carcinoma (ESCC). Recent studies have revealed that several genes and molecules are involved in the origin and progression of ESCC. Tumour progression and metastasis require angiogenesis. It has recently been reported that vascular endothelial growth factor C (VEGF-C) induces not only angiogenesis but also lymphangiogenesis via VEGF receptor-2 and VEGF receptor-3. Aim : To investigate the correlation between VEGF-C expression and tumour metastatic recurrence in patients with ESCC. Material and methods : Ninety-two ESCC specimens were re-evaluated by reverse transcriptase-polymerase chain reaction (RT-PCR) to detect VEGF-C mRNA. The correlation between VEGF-C expression and clinicopathological factors was analysed using Fisher’s exact probability test or χ 2 test. The log-rank test was used to calculate the recurrence difference. And Cox regression multivariate analysis was performed to determine independent prognostic factors. Results : The VEGF-C mRNA expression was correlated with pT, pN, pTNM and lymphatic invasion. The 5-year tumour metastatic recurrence rate in patients after operation was significantly associated with pT, pN, pTNM stage and VEGF-C mRNA expression. The 5-year tumour metastatic recurrence rate of patients with VEGF-C mRNA expression in oesophageal cancer tissues was significantly higher than that of the patients without VEGF-C mRNA expression. The results of Cox regression multivariate analysis confirmed that pT status and VEGF-C mRNA expression were independent relevant factors. Conclusions : The VEGF-C expression is related to tumour invasion, lymphatic invasion, lymph node metastasis, tumour stage and tumour metastatic recurrence in ESCC patients.